2011
DOI: 10.1159/000333091
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status and Analysis of Efficacy and Safety of Ferric Carboxymaltose Treatment in Patients with Inflammatory Bowel Disease

Abstract: Background and Aims: We analyzed iron deficiency and the therapeutic response following intravenous ferric carboxymaltose in a large single-center inflammatory bowel disease (IBD) cohort. Methods: 250 IBD patients were retrospectively analyzed for iron deficiency and iron deficiency anemia. A subgroup was analyzed regarding efficacy and side effects of iron supplementation with ferric carboxymaltose. Results: In the cohort (n = 250), 54.4% of the patients had serum iron levels ≤60 µg/dl, 81.2% had ferritin ≤10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…ID in patients with IBD has been reported to be around 40% and even as high as 80%. 26,27 Our study, although not directly designed to determine the prevalence of ID in IBD, confirms that ID is frequent, as we found that 43% of included patients were iron deficient. ID usually goes unrecognized and little is known about its clinical impact.…”
Section: Discussionsupporting
confidence: 63%
“…ID in patients with IBD has been reported to be around 40% and even as high as 80%. 26,27 Our study, although not directly designed to determine the prevalence of ID in IBD, confirms that ID is frequent, as we found that 43% of included patients were iron deficient. ID usually goes unrecognized and little is known about its clinical impact.…”
Section: Discussionsupporting
confidence: 63%
“…Most trials 14,22,42,45,46,[48][49][50][51][52][53][54][55] included adult patients only (≥18 years), while two additionally enrolled adolescent IBD patients ≥16 years 43 or ≥15 years, 44 respectively. Garcia-Lopez et al included adults and adolescents ≥15 years, stating a mean of 42.8 years and SD 16.3.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Records excluded on full text (n = 10) Not RCT: 9 Not exclusively iron monotherapy: 1 studies of various designs were included in the systematic review. 14,[43][44][45][46][48][49][50][51] One small crossover study 56 was carefully considered for inclusion but finally excluded on the grounds of a lack of sufficient data on response rates and missing confirmation of anaemia before the second study phase. In summary, the systematic review included six RCTs and nine studies of other designs assessing the efficacy of specific intravenous iron solutions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations